Descriptions of Netechmodes gen. n. and two species of Netechma Razowski, 1991 from Ecuador (Lepidoptera Tortricidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
One new genus (Netechmodes) and three new species (Netechmodes harpago, Netechma selecta, N. phobetrovalva) are described from Ecuador.